Rider Payroll Information System at Mini Station Ninja Xpress Sidoarjo - Arif Muhammad Rizal; Lukman Junaedi (Journal of Science Technology (JoSTec), 2026)
Information system products are needed in the current era of technological development. The existence of an information system can replace manual calculation systems that have been used for many years, one example being the payroll information system. Although payroll systems have been implemented in several large companies in Indonesia, PT. Andiarta Muzizat (Ninja Xpress), which operates in package delivery services, has not fully implemented a payroll information system, especially for riders (couriers). Therefore, this study aims to develop a payroll information system that can calculate rider salaries quickly and in detail. The system is designed to minimize discrepancies in salary calculations and provide transparent payroll information. This research was conducted at Mini Station Ninja Xpress Sidoarjo. The system development uses the Extreme Programming (XP) method, which includes planning, design, coding, and testing stages. The result of this research is a web-based payroll information system built using PHP and MySQL that is capable of calculating rider income, including gross salary, bonuses, and net salary received each month. The implementation of this system is expected to improve accuracy, efficiency, and transparency in payroll processes and reduce disputes related to salary discrepancies among riders.